KAJIAN DAYA TAMPUNG BEBAN PENCEMAR SUNGAI CIUJUNG KABUPATEN SERANG PROVINSI BANTEN - Pramuswara, Alfian Pradigda; Fachrul, Melati Ferianita; Astono, Widyo (JURNAL PENELITIAN DAN KARYA ILMIAH LEMBAGA PENELITIAN UNIVERSITAS TRISAKTI, 2024)
This Final research was conducted in Ciujung River where this research was conducted in Serang Regency with its head in Nagara Village, Serang Regency, and downstream in Tirtayasa Village, Serang Regency. The research was conducted for 3 months from October – December 2022 starting from 09.00 – 12.00 and continuing from 12.00 – 13.45. The purpose of the study is to identify and determine the sources of pollution that have the potential to pollute the Ciujung River, analyze water quality, water quality status, and pollutant levels in the Ciujung River, and analyze the carrying capacity of polluter loads in the Ciujung River. And analyze the burden of pollutants in the Ciujung River. The length of the Ciujung River studied is 31.3 km. The parameters used for this study are pH, Temperature, DO, BOD, COD, Nitrate, Phosphate, and Total Coliform. The method used in identifying the source of pollution contained in the Ciujung River is carried out by conducting field observations and taking samples of Ciujung River water. Sampling in the Ciujung River was carried out by the grab sampling method. which is done at 6 sampling points. Analysis of river water quality was carried out at the Trisakti University Laboratory. The results of the analysis are then compared with the quality standards of PP No. 22 of 2021 in Attachment VI. Water Quality Status is calculated by the Polluter Index method. Nonpoint sources of pollution are dominated by residential areas, stalls, garbage, shops, mosques/prayer rooms, schools, and markets. Point sources of pollution are obtained from industrial areas. Measurement of river characteristics is carried out in October, November, and December by measuring distance, width, depth, cross-sectional area of the river, river speed, and river discharge. The results of the analysis of water quality in the river stated that for phosphate parameters almost all exceeded quality standards due to domestic waste from the environment, the runoff of agricultural fertilizers, livestock waste, and very high industrial activities. The BOD parameters at point 2 and point 5 exceed the quality standards due to the content of organic waste. The load capacity of BOD pollutants is 3.64 kg/day – 20.20 kg/day, COD is 42.63 kg/day – 144.22 kg/day, Nitrate is 1.67 kg/day – 3.47 kg/day, Phosphate 0.79 kg/day – 3.11 kg/day, Total Coliform is 8694.19 kg/day – 33042.56 kg/day. BOD Pollution Load of 314.26 kg/day- 1744.99 kg/day COD of 2365.46 kg/day - 12460.37 kg/day Nitrate of 144.55 kg/day- 423.16 kg/day Phosphate of Total Coliform of 454133.37 kg/day – 2854876.86 kg/day.